Inside Cover: Selective Autonomous Molecular Transport and Collection by Hydrogel‐Embedded Supramolecular Chemical Gradients (Angew. Chem. Int. Ed. 50/2019). Issue 50 (12th November 2019) - Zhang, Shiyan; Zhang, Chunjie; Chen, Hao; Kieffer, Spencer J.; Neubrech, Frank; Giessen, Harald; Alleyne, Andrew G.; Braun, Paul V.
Abstract : Chemical‐gradient‐driven concentration enhances the sensitivity and selectivity of chemical sensors. In their Communication on page 18165, P. V. Braun et al. show how hydrogel‐embedded radially symmetric cyclodextrin gradients direct transport of molecules including the nerve agent simulant 4‐methylumbelliferyl phosphate. To provide near real‐time read‐out of the analyte concentration an array of IR‐resonant metallic nanoantennas was used to enhance the IR signal generated by the analyte.